MODEL BISNIS CANVAS PADA BISNIS WEDDING ORGANIZER DI BATAM - Purba, Tiurniari; Nainggolan, Nora Pitri (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2023)
As time progresses, many people are starting to realize the existence of wedding organizers (WO) and are starting to use their services. This is because prospective brides and grooms, most of whom are millennials, are busy with their respective jobs. Because of this busy schedule, prospective brides and grooms find it difficult to prepare everything related to their wedding. This is where the WO's job is needed to help the smooth running of a wedding party. Starting from the contract/blessing to the reception process. Running a business is not enough to just rely on a model, because in reality every business or undertaking requires its own elements. This research aims to analyze a wedding organizer business. The model used to help manage this business is the business canvas model (MBC) which consists of nine elements guided by SWOT analysis. SWOT analysis will really help manage a business starting from describing strengths, weaknesses, opportunities and threats. This research focuses more on how to manage the WO business with MBC. The research results explain that before running a WO business, MBC is a tool in management strategy to translate concepts, consumers, infrastructure and company finances in the form of visual elements. With the MBC framework, it is very easy for WO business to be realized quickly and on target.